The above problem was asked in a test. I got the wrong answer because I solved it in the following way.
BW without FB = 1000 - 100 = 900
BW with FB = BW without FB * (1+A*beta) = 900 * 100 = 90kHz
I understand that both both the formulae are different and both can't be right at the same time. But my book mentions below 3 formulae bcz of which I got confused in the test.
BW with FB = BW without FB * (1+A*beta)
fH with FB = fH without FB * (1+A*beta)
fL with FB = fL without FB / (1+A*beta)
Please guide me on this, which formulae to use ?